Fine needle cytology of Kaposi’s sarcoma in heterosexual male - Dhote, Anjali R.; Umap, Pradeep; Shrikhande, Anuradha (International Journal of Research in Medical Sciences, 2017)
Kaposi’s sarcomas the most common malignancy associated with Human Herpesvirus-8 (HHV8) infection. Though name is sarcoma but it is low grade vascular neoplasm. It is the tumour which arises from endothelial lining of vessels as well as lymphatic channels. So it involved all sites such as skin, Gastro intestine, lungs along with lymph nodes. We are presenting one such case of 65 year immunocompromised Indian male presented with multiple non blanching reddish bluish nodules on all extremities, chest, back with submandibular and cervical lymphadenopathy. Fine needle aspiration cytology (FNAC) was performed and diagnosis was given low grade spindle cell neoplasm consistent with Kaposi’s sarcoma which was confirmed on histopathology as Kaposi’s sarcoma.